Degraded perceptual and affective processing of racial out-groups: An electrophysiological approach. (4th July 2017) - Sheng, Feng; Du, Na; Han, Shihui
ABSTRACT: Human beings process perceptual and affective information of racial out-groups in a degraded manner. Relative to racial in-group members, we lack perceptual individuation of racial out-group members and empathize their pain to a less degree. To date, however, the relationship between the deficiency of individuation and the impairment of empathy in responding to racial out-groups remains elusive. By recording event-related brain potentials in response to racial in-group and out-group faces portraying pain and neutral expressions, we simultaneously measured neural activity that underpinned individuation and empathy. Deficiency in individuating members of racial out-groups, manifesting as reduced reactivity of face-sensitive N170 in the occipitotemporal region of the brain, predicted attenuation of fronto-central empathic response to the suffering of racial out-groups. Further, the individuation bias mediated the influence of racial prejudice on racial in-group bias in empathic neural responses. These findings suggest an interplay between degraded perceptual and affective processing of racial out-groups.